Republic of Mozambique : Second Review Under the Policy Support Instrument and Request for Waiver of Nonobservance of Assessment Criteria; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Mozambique. (IMF Staff Country Reports; Country Report ;, 2008)
This paper discusses key findings of the Second Review Under the Policy Support Instrument for Mozambique. Overall performance under the program was satisfactory but encountered unexpected challenges. Domestic revenues were stronger than envisaged, but the end-December 2007 assessment criterion (AC) on net credit to government (NCG) was missed largely because of aid shortfalls for onlending to public enterprises and deficiencies in cash-flow management that are being addressed. Monetary policy remained prudent, but the end-year AC on reserve money was missed.